Model Pendidikan Karakter Di Lingkungan Keluarga Selama Pembelajaran Jarak Jauh Di Masa Pandemi Covid – 19 (Studi Kasus Pada Orang Tua Siswa Sd Rusyda Medan) - Batubara, Hawari; Muhaimin, Abdul; Hamida, Prismar; Siagian, Sahputra; Giprakoso, Abdi (Al-Ulum: Jurnal Pendidikan Islam, 2020)
This study aims to determine student learning activities while studying at home, to find out what character values can develop during learning at home, to find out the causes of the good development of these character values. This study used a qualitative research method with case studies on the parents of students of SD Rusyda Medan. The data were obtained by interviewing the parents of students. The results of this study indicate the development of character education and the relationship between children and parents is quite good during learning from distance or at home. The character values that can be developed from activities carried out by students at home are (1) religious character values, (2) disciplinary character values, (3) creative character values, (4) curiosity character values. The development of these character values is the result of the synergy of teachers and parents in guiding students lovingly, interacting, and doing positive activities together during this COVID-19 pandemic.Â Keywords: Model, Education, Character, parents, Students